2021
DOI: 10.3389/fonc.2020.610663
|View full text |Cite
|
Sign up to set email alerts
|

Posttranslational Modifications of Smurfs: Emerging Regulation in Cancer

Abstract: Smad ubiquitination regulatory factors (Smurfs) belong to the Nedd4 subfamily of HECT-type E3 ubiquitin ligases. Under normal situations, Smurfs are exactly managed by upstream regulators, and thereby strictly control tumor biological processes, including cell growth, differentiation, apoptosis, polarization, epithelial mesenchymal transition (EMT), and invasion. Disruption of Smurf activity has been implicated in cancer progression, and Smurf activity is controlled by a series of posttranslational modificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 110 publications
0
4
0
Order By: Relevance
“…The activity of TGF-β/Smad pathway is known to be regulated by ubiquitination at multiple levels [ 25 ]. As E3 ubiquitin ligases, Smad ubiquitination regulatory factors (Smurfs) play an important role in mediating the ubiquitination and degradation of TGF-β/Smad pathway proteins [ 26 ]. Therefore, we speculated that ARK5 regulates TβRI and Smad4 degradation by modulating the expression of Smurfs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The activity of TGF-β/Smad pathway is known to be regulated by ubiquitination at multiple levels [ 25 ]. As E3 ubiquitin ligases, Smad ubiquitination regulatory factors (Smurfs) play an important role in mediating the ubiquitination and degradation of TGF-β/Smad pathway proteins [ 26 ]. Therefore, we speculated that ARK5 regulates TβRI and Smad4 degradation by modulating the expression of Smurfs.…”
Section: Resultsmentioning
confidence: 99%
“…Our further studies confirmed that TβRI and Smad4 are indeed degraded by ubiquitination. Smurfs belong to the Nedd4 subfamily of HECT-type E3 ubiquitin ligases and are involved in the ubiquitination and degradation of various TGF-β pathway-related proteins [ 26 ]. Therefore, we next tested whether knockdown of ARK5 could affect the expression of Smurfs.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, a growing number of evidence has suggested that PTM was closely related to cell survival, cell cycle, differentiation, and innate and adaptive immunity for multiple cancer ( Wu et al, 2019 ; Chen et al, 2020 ; Yang et al, 2020 ). As one of the most important PTM, ubiquitination has also attracted much attention in OS ( Chen et al, 2014 ; Ying et al, 2016 ; Zhao et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Research by Yang L et al demonstrates that the functional activity of Smurfs is regulated by an array of PTMs, including phosphorylation, ubiquitination, demethylation, and methylation. These modifications are critical in orchestrating the dynamic processes associated with EMT and subsequent tumor invasion [ 38 ]. This suggests that targeting PTMs to modulate EMT could be a viable strategy to impede tumorigenesis and the development of cancer stem cells.…”
Section: Ptms and Emtmentioning
confidence: 99%